"Ask Me and I Will Tell You": Gifted Boys' Perceptions of Self and School. Issue 1 (January 2020) - Watts, Jessica
Using the Frame of Reference lens developed by Marsh, this article explains how elementary-age gifted boys construct their self-perceptions as learners by comparing their academic abilities with those of their peers. Understanding giftedness defined as a social construct, this article discusses an ethnographic study that examines gifted boys' self-perceptions and their teachers' perceptions of them as learners. Data collected from observations and interviews are analyzed to discuss the study's findings that are explored through three themes. First, the participants want their teachers to understand that although they value their gifted identities, they still have academic needs for which they need help. Second, gifted boys believe their classroom behaviors are often misunderstood. Third, the participants want a voice about the curriculum assigned to them. These findings conclude by examining implications for teachers to address the perceptions of boys as students in their classrooms.